Analisis strategi penanganan pembiayaan bermasalah pada bmt sarana wiraswata muslim - Azkya, Vaizul (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the causes of non-performing financing and the strategies implemented to address them at BMT Sarana Wiraswasta Muslim in Malang. Using a descriptive qualitative approach through interviews, observations, and secondary data, the research reveals that problematic financing is mainly caused by three factors: members’ business conditions, members’ character, and weaknesses in cooperative management. To overcome these issues, BMT applies strategies based on sharia principles, namely rescheduling (payment rescheduling), reconditioning (contract adjustment), kafalah (guarantee), and collateral execution as the final measure. These strategies not only safeguard BMT’s financial sustainability but also uphold justice, solidarity, and mutual assistance in the framework of Islamic economics. The findings are expected to enrich the literature on Islamic financing management and provide practical insights for BMT managers and similar institutions in effectively handling non-performing financing.